2013
DOI: 10.1017/s0954422413000097
|View full text |Cite
|
Sign up to set email alerts
|

Non-extractable polyphenols, a major dietary antioxidant: occurrence, metabolic fate and health effects

Abstract: Current research on dietary antioxidants misses the so-called non-extractable polyphenols (NEPP), which are not significantly released from the food matrix either by mastication, acid pH in the stomach or action of digestive enzymes, reaching the colon nearly intact. NEPP, not detected by the usual analytical procedures, are made up of macromolecules and single phenolic compounds associated with macromolecules. Therefore, NEPP are not included in food and dietary intake data nor in bioavailability, interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(162 citation statements)
references
References 96 publications
(190 reference statements)
3
154
0
5
Order By: Relevance
“…After their colonic fermentation, they release metabolites that may either have a local beneficial effect or be absorbed, reaching paslma at longer times than soluble antioxidants and giving place to potential systemic effects, including imporvemnts in CVD risk factors. All these aspects wre recently reviewed (Pérez-Jiménez et al, 2013). Further studies should explore whether the differences in MACAN intake described here for different countries are associated with reduced risk for different chronic diseases.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
See 1 more Smart Citation
“…After their colonic fermentation, they release metabolites that may either have a local beneficial effect or be absorbed, reaching paslma at longer times than soluble antioxidants and giving place to potential systemic effects, including imporvemnts in CVD risk factors. All these aspects wre recently reviewed (Pérez-Jiménez et al, 2013). Further studies should explore whether the differences in MACAN intake described here for different countries are associated with reduced risk for different chronic diseases.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…Although studies of the health effects of NEPP are scarce, they have shown promising results in relation to gastrointestinal health (including colorectal cancer) and CVD (Pérez-Jiménez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysable tannins content (NEPP) was higher in mango, whereas peach and guava by-products presented the greatest values of condensed tannins. The NEPP from the juice byproducts could exert an important beneficial effect in the colon, promoting the intestinal health through the increase in antioxidant and antiproliferative capacities (Pérez-Jiménez et al, 2013).…”
Section: Characterization Of Nutraceutical Compounds Of Juice By-prodmentioning
confidence: 99%
“…The polyphenols can be absorbed in the small intestine (extractable polyphenols) (EPP), or reach colon along with other indigestible compounds like dietary fibre, resistant protein, starch, among others (nonextractable polyphenols) (NEPP). ADF can be fermented by bacterial microflora, and their metabolites have been reported to exert greater beneficial effects than their precursors (Pérez-Jiménez, Díaz-Rubio, & Saura-Calixto, 2013;Saura-Calixto, 2010). Therefore, sources of these nutraceutical compounds, such as juice by-products, are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…The particular antioxidant vehicle for the study (a commercial pomegranate and grape juice), as well as the dose, were chosen based on: a) dietary AC in Spain having decreased approximately 2000 μmol Trolox units per day since the 1960s [7], so this dose would be equivalent to a return to the traditional Mediterranean dietary pattern in terms of AC; b) a commercial processed product providing a standardized antioxidant content; and c) antioxidants from a beverage being more accessible in the small intestine than those from solid food, where a fraction of the polyphenols is associated with other components of the food matrix [19]. It is notable that for the ARJ chosen, this AC corresponds to a glass a day.…”
Section: Resultsmentioning
confidence: 99%